Pemberdayaan UMKM Masyarakat Dalam Pembuatan Tempe Berbahan Dasar Kedelai Di Desa Prajegan Kecamatan Sukorejo Kabupaten Ponorogo - Najib, Muhamad; Asfahani, Asfahani; Fathoni, Khoirul (Social Science Academic, 2024)
Tempeh is made by drying soybeans, which are a good source of nutrition for plants. Making tempeh from soybeans is difficult because of the high price of soybeans and the decline in domestic soybean production, so tempe makers have to think about solutions to these problems. This research was conducted at the tempe making industry located in Prajegan Village, Sukorejo District, Kab ponorogo. The method used in this research is community-based development (ABCD) This service method takes the form of training, which is aimed at KPM students to provide knowledge and soft skills to the training participants.The impact of the training conducted has shown effects, reflected in reactions, learning, behavioral changes, and the results of the training. The participants have completed the training with good skills, making their work more efficient and effective. The chosen business partner is a home industry producing tempeh owned by Mrs. Mariatun. which goes through the production process: soaking, milling, washing, boiling, circulation, fermentation, packaging . The idea for empowering home industry tempe SMEs that are environmentally friendly is to optimize the active participation of owners in innovating and partnering in the processing of tempe home industry production results. This activity took place on July 14, 2024, and was dominated by KPM participants, and it was carried out successfully. Through this activity, participants learn about the health benefits of processed tempeh due to its relatively high nutritional content. Additionally, participants can understand the process and methods of making tempeh, which can become a promising business opportunity